Face Recognition using Eigenfaces and Distance Classifiers (International Journal of Engineering and Computer Science, 2017)
facial recognition is a computer application composes for complex algorithms that use mathematical and matricial techniques, these get the image in raster mode(digital format) and then process and compare pixel by pixel using different methods for obtain a faster and reliable results, obviously these results depend of the machine use to process this due to the huge computational power that these algorithms, functions and routines requires. The main goal of this paper is show and explains the easiest way to implement a face detector and recognizer in real time for multiple persons using Principal Component Analysis (PCA) with eigenfaces,distance measures.